Contaminant metals in black scabbard fish (Aphanopus carbo) caught off Madeira and the Azores - Afonso, C. (2015)
Total mercury, cadmium and lead concentrations were measured in black scabbard fish (Aphanopus carbo), caught off Madeira and the Azores archipelagos (Portugal). The metal contents were expressed in mg kg(-1) wet weight. The mean mercury levels in liver were 4.50 and 2.37 whereas, in skin, such values were 0.59 and 0.36 (Madeira and Azores, respectively). Onaverage, the muscle content was around 0.9 in fish from both areas. Cadmium maximum levels in muscle and skin were found in Azores samples (0.09 and 0.11, respectively). Mean lead contents in all samples were always below than 0.10. In general, the results obtained did not allow the establishment of any relationship between metal accumulation and fish weight or length. According to the permissible WHO and FAO levels, these results, suggest that this species does not represent a risk for human consumption if the liver is excluded and the edible part consumed with moderation. (c) 2006 Elsevier Ltd. All rights reserved.